1998
DOI: 10.1163/156853998792913519
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Behaviour in Roach Shoals: The Role of Body Length and Nutritional State

Abstract: This study investigated the positioning behaviour of individual fish in small shoals of 2 and 10 roach, Rutilus rutilus. In pairs consisting of one small and one large fish with an average length difference of 10 mm, no difference was observed in the number of initiations of shoal movement between small and large fish. However, once both fish were moving, large fish took up the front position more frequently than small ones. A subsequent experiment showed that body length was positively correlated with swimmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…Instead, faster, larger birds emerge as leaders (Pettit et al, 2015, 2013; Herbert-Read, 2015). Similar results have been found in other taxa – larger roach ( Rutilus rutilus ), for example, occupy positions at the front of groups (Krause et al, 1998; Krause et al, 2000). Therefore, differences in individuals' body size and self-assortment as a result of preferred speed can lead to certain individuals disproportionally influencing others' movements.…”
Section: Group and Individual Variationsupporting
confidence: 88%
“…Instead, faster, larger birds emerge as leaders (Pettit et al, 2015, 2013; Herbert-Read, 2015). Similar results have been found in other taxa – larger roach ( Rutilus rutilus ), for example, occupy positions at the front of groups (Krause et al, 1998; Krause et al, 2000). Therefore, differences in individuals' body size and self-assortment as a result of preferred speed can lead to certain individuals disproportionally influencing others' movements.…”
Section: Group and Individual Variationsupporting
confidence: 88%
“…Although positional preferences have been observed in schools in relation to the physiological state of each individual (e.g. hunger level, Krause et al 1998), schooling is a dynamic behaviour, and most fish continuously change positions from trailing to leading (Krause 1993(Krause , 1994Domenici et al 2002). A relatively constant reshuffling rate was found in schools of herring Clupea harengus which decreased when fish were exposed to hypoxia (Domenici et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The positioning of each fish in a school is the result of a number of trade-offs. For instance, leading positions may be chosen by hungry individuals, since they would react more strongly to smells or other cues from food sources, although they may also experience a higher risk of predation (Krause 1993, Bumann et al 1997, Krause et al 1998. Energetically, trailing individuals can enjoy energetic advantages, although in the case of relatively large schools, trailing individuals may experience a further reduction in oxygen level due to the oxygen consumption of fish in the front (McFarland & Moss 1967, Domenici et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reebs (2001) also found an influence of body size on leadership with large knowledgeable fish being readily followed by small uninformed fish whereas small knowledgeable fish were less readily followed by larger individuals. Krause et al (1998) found that front positions tended to be occupied by larger fish and food-deprived fish. Bumann et al (1997) showed that individuals in front positions in shoals of roach R. rutilus led the group, finding that just a single individual in a front position could have a strong influence on an entire shoal of 16 fish.…”
Section: Introductionmentioning
confidence: 92%